Health students' knowledge assessment on the Glasgow Coma Scale at the University of Minas Gerais (Research, Society and Development, 2021)
Introduction: health care students need to have full knowledge of awareness assessment methods for excellence in professional practice and patient care, however, the literature reports health professionals' shortcomings in the use of the Glasgow Coma Scale (ECG). Objective: The aim of the present study was to analyze and assess the knowledge of healthcare students about the function and applicability of the Glasgow Coma Scale (ECG). Methods: data were generated by applying a questionnaire to senior students of Medicine, Nursing, Dentistry and Pharmacy courses at the Federal University of Alfenas. Results and Discussion: the results reveal that future doctors and nurses have greater knowledge of the parameters and application of ECG when compared to other evaluated students, this is an obstacle to excellence in health care, since multidisciplinary teams are extremely important for care, and its members need an expanded knowledge of ECG to provide the patient with serial monitoring and avoid communication problems between the team. Conclusion: there is a deficit in learning about ECG among students in the health field and, in order to supply it, universities must commit to offering theoretical and practical courses on the use of ECG.